Concentration of salivary immunoglobulin A, in relation to periodontal disease, plaque, and calculus - Mona Shah; Yogesh Doshi; S H Hirani (Wolters Kluwer Medknow Publications, 2010)
Background: It has become apparent that every pathologic process in the body involves the immune system. Periodontal inflammation is not an exception. Periodontal health depends on the interaction of microbial flora and host response. Since long, research is focused on understanding the immunopathologic mechanism operating in the development and maintenance of periodontal inflammatory changes. Methods: Patients of age 20-35 were selected. Nonstimulated saliva was collected and assessed using radial immunodiffusion assay to estimate levels of IgA. Results: The present study suggests patients with gingival index 0.2-0.5 and periodontal index 0 have a concentration of IgA less than 21.4%. As values of gingival and periodontal index go on increasing, the concentration of salivary IgA also increases. Conclusion: the concentration of salivary IgA is directly and positively correlated to severity of inflammation. Also the concentration of IgA depends on the presence of plaque.